Testicular Germ Cell Tumor Metastatic to the Right Atrium - ÖZBEN SADIÇ, BESTE; TÜRKÖZ, HÜSEYİN KEMAL; AK, KORAY; ARSAN, SİNAN (WILEY-BLACKWELL, 2011)
P>We describe a right atrial metastasis of a testicular germ cell tumor, which was successfully removed from the tricuspid valve and subvalvular apparatus without the need for valve replacement. (J Card Surg 2011;26:276-279).